2023
DOI: 10.1039/d2tc04789f
|View full text |Cite
|
Sign up to set email alerts
|

Color-tunable and ultralong organic room temperature phosphorescence from poly(acrylic acid)-based materials through hydrogen bond engineering

Abstract: Color-tunable and ultralong organic room temperature phosphorescence (URTP) materials have drawn extensive attention due to their various applications in many fields. Herein, a series of poly(acrylic acid) (PAA)-based RTP materials...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Thus, it can be concluded that the water molecules entering the RTP paper can break the hydrogen bonds between the cellulose chains, disrupting the rigid environment and quenching the RTP. [ 27n,29 ] When the RTP paper was treated with heat, the cellulose intermolecular hydrogen bonds were formed again, recovering the RTP (Figure 3h). It is worth noting that there was almost no change in the phosphorescence intensity of the RTP paper stored under ambient conditions for 15 days, and the afterglow colors of RTP paper were not affected even when exposed to sunlight (Figures S31 and S32, Supporting Information), indicating the excellent stability of the RTP paper in the practical environment.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it can be concluded that the water molecules entering the RTP paper can break the hydrogen bonds between the cellulose chains, disrupting the rigid environment and quenching the RTP. [ 27n,29 ] When the RTP paper was treated with heat, the cellulose intermolecular hydrogen bonds were formed again, recovering the RTP (Figure 3h). It is worth noting that there was almost no change in the phosphorescence intensity of the RTP paper stored under ambient conditions for 15 days, and the afterglow colors of RTP paper were not affected even when exposed to sunlight (Figures S31 and S32, Supporting Information), indicating the excellent stability of the RTP paper in the practical environment.…”
Section: Resultsmentioning
confidence: 99%
“…(a) Chemical structure of the doped phenylboronic acid and benzoic acid derivatives and photographs of PAA-based RTP materials with a 1000:15 molar ratio of AA to the doped luminophores under 254 nm UV light and after ceasing of irradiation under ambient conditions. Reproduced with permission from ref . Copyright 2023 Royal Society of Chemistry.…”
Section: Construction Of Polymer-based Rtp Systemsmentioning
confidence: 99%
“…In 2023, Li et al 24 developed a series of poly(acrylic acid) (PAA)-based RTP materials. A series of phenylboric acid and benzoic acid derivatives, CPBA, BDA, PBA, TPA, and BA, were selected as luminophores to ultimate hydrogen bond with the PAA matrix (Figure 3a).…”
Section: Polymers Doped With Organic Luminophorementioning
confidence: 99%
“…These materials can continue emitting light even after the cessation of excitation by an external light source. This feature endows OLPL materials with vast prospects for application across many fields, including anti-counterfeiting, 1–3 encryption, 4–7 and biological imaging. 8,9 At present, researchers have explored many strategies for constructing organic long-persistent luminescent materials, such as polymerization, 9,10 aggregation, 11,12 introduction of heavy atoms, 13,14 host–guest (H–G) doping, 15–18 and multi-component doping.…”
Section: Introductionmentioning
confidence: 99%